2022
DOI: 10.3389/fped.2022.1044210
|View full text |Cite
|
Sign up to set email alerts
|

NEO-SPEAK: A conceptual framework that underpins breaking bad news in neonatology

Abstract: ObjectiveBreaking bad news in neonatology is a frequent and difficult challenge. Although there are guidelines for communicating with parents in pediatrics and neonatology, the specific framework for breaking bad news in neonatology has not been studied in more detail. Therefore, we aimed to identify determinants that are important for successful managing breaking bad news in neonatology from professionals' perspective and to develop a conceptual framework that underpins this challenging task.MethodsWe conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Most importantly, parents and families require compassionate care, honesty about the accuracy of precise predictions, and explicit messages that medicine will be there as a resource for health, developmental, and family support. In this era of far-from-adequate medical homes and community support, health professionals must create shared decision making with practical updates across systems of care [10][11][12][13][14][15][16][17], Health professionals need also to recognize that past practices of communicating "the bad news about disability" in a few short counseling sessions before discharge is not sufficient [18][19][20]. They benefit from both simulated experiences and broader literature including lived experiences about disability and shared decision making [11][12][13][14][15][16][17].…”
Section: Beginnings: Partnering With Familiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Most importantly, parents and families require compassionate care, honesty about the accuracy of precise predictions, and explicit messages that medicine will be there as a resource for health, developmental, and family support. In this era of far-from-adequate medical homes and community support, health professionals must create shared decision making with practical updates across systems of care [10][11][12][13][14][15][16][17], Health professionals need also to recognize that past practices of communicating "the bad news about disability" in a few short counseling sessions before discharge is not sufficient [18][19][20]. They benefit from both simulated experiences and broader literature including lived experiences about disability and shared decision making [11][12][13][14][15][16][17].…”
Section: Beginnings: Partnering With Familiesmentioning
confidence: 99%
“…In this era of far-from-adequate medical homes and community support, health professionals must create shared decision making with practical updates across systems of care [10][11][12][13][14][15][16][17], Health professionals need also to recognize that past practices of communicating "the bad news about disability" in a few short counseling sessions before discharge is not sufficient [18][19][20]. They benefit from both simulated experiences and broader literature including lived experiences about disability and shared decision making [11][12][13][14][15][16][17]. Too often, health professionals fail to acknowledge that much past information about intellectual disability left families stigmatized and isolated, and often blamed parents for not accepting outdated information [21,22].…”
Section: Beginnings: Partnering With Familiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous analyses we defined determinants influencing BBN in neonatology [33] and compared parental preferences with their actual BBN experiences [34] and found that BBN not only burdened the recipients but also the messengers. The majority of parental top preferences differed significantly in their implementation in the real-life interview, and a compassionate delivery of bad news correlated highest with a parent-rated quality of BBN conversation.…”
Section: Introductionmentioning
confidence: 99%